mTORC1 and mTORC2 are differentially engaged in the development of laser-induced CNV - Jin Young Yang; Sanjar Batirovich Madrakhimov; Dong Hyuck Ahn; Hun Soo Chang; Sang Joon Jung; Seung Kwan Nah; Ha Yan Park; Tae Kwann Park (Cell Communication and Signaling, 2019)
Abstract Background The mechanistic target of rapamycin (mTOR) pathway is a potential target to inhibit pathologic processes in choroidal neovascularization. However, the exact role of mTOR signaling in the development of CNV remains obscure. In this study, we assessed the role of mTORC1 and mTORC2 as well as the effect of rapamycin (sirolimus) on choroidal neovascularization (CNV) in a laser-induced mouse model. Methods In experiment A, we observed the natural course of CNV development and the dynamics of mTOR-related proteins during the 12 days after the laser injury. The expression of mTOR-related proteins was evaluated using Western blot (WB). Cryosections of CNV-induced mice were immunostained for the visualization of the vascular and extravascular components of the CNV. Experiment B was performed to confirm the critical period of mTOR signaling in the development of laser-induced CNV, we administered rapamycin before and/or during the active period of mTOR complexes. WB and immunofluorescence staining was performed to evaluate the mode of action and the effect of mTOR inhibition on CNV development. Results In experiment A, we detected high levels of p-mTOR S2448 and p-mTOR S2481 from the 5th to 12th day of laser injury. Immunofluorescence imaging of cryosections of mice sacrificed on day 7 revealed greater co-immunoreactivity of p-mTOR S2448 positive cells with CD11b and F4/80, while p-mTOR S2481 positive cells showed colocalization with CD31, α-SMA, and cytokeratin. In experiment B, rapamycin injection during the active period of mTOR signaling demonstrated near-complete inhibition of CNV lesion as well as significant induction of autophagy. Conclusion Our study suggests the mTOR as a critical player during CNV development in laser-induced mouse model through differentially acting with the mTORC1 and mTORC2. mTORC1 activity was high predominantly in inflammatory cells in CNV lesion, while mTORC2 activity was higher in vascular components and the RPE.